Equilibrium and kinetic study and modeling of Cu(II) and Co(II) synergistic biosorption from Cu(II)-Co(II) single and binary mixtures on brown algae C. indica. Issue 1 (March 2015) - Akbari, Masoumeh; Hallajisani, Ahmad; Keshtkar, Ali Reza; Shahbeig, Hossein; Ali Ghorbanian, Sohrab
Highlights With chemical processing by NaCl, maximum biosorption was investigated. It was found uptake process followed the pseudo-second order expression. Langmuir isotherm fitted better than the others for Cu and Temkin isotherm for Co. In binary system, the extended Freundlich isotherm fitted better than the others.